(untitled) (The Journal of Geography Education in Africa, 2025)
A key responsibility of academic scholarship is to contribute to and further develop the field of enquiry. This paper offers a critical qualitative reflection on how South African Geography Education (GE) scholars are contributing to and advancing the field of enquiry from the perspective of the International Geographical Congress (IGC). This event, held every four years, is the largest gathering of geography scholars and researchers in some 43 commissions, one of which is GE, in the world. The two-part analysis provides an overview of who is producing knowledge and where it is being produced in the Global North and Global South. This is followed by a thematic analysis of the abstracts of the South African papers. The findings affirm the scholarly contribution our scholars are making to the field individually and in collaboration with colleagues and postgraduate students. Secondly, the findings reveal an unevenness in terms of who is contributing, and it highlights constraining factors impeding participation. The paper concludes by making some tentative propositions on a future research agenda that may help to advance the field and how constraining factors may be addressed so that we cultivate a stronger, more inclusive, Global South voice in the field.